Step 1: Rewrite the quadratic expression inside the square root. We can complete the square for \( 4x - x^2 \):
\[
4x - x^2 = 4 - (x - 2)^2.
\]
Thus, the integral becomes:
\[
\int \frac{1}{\sqrt{4 - (x - 2)^2}} \, dx.
\]
Step 2: Use the standard trigonometric substitution \( x - 2 = 2 \sin \theta \). Then, \( dx = 2 \cos \theta \, d\theta \), and the expression inside the square root becomes:
\[
4 - (x - 2)^2 = 4 - 4 \sin^2 \theta = 4 \cos^2 \theta.
\]
So, the integral simplifies to:
\[
\int \frac{2 \cos \theta}{2 \cos \theta} \, d\theta = \int d\theta.
\]
Step 3: Integrating \( d\theta \), we get:
\[
\theta + C.
\]
Step 4: Substitute \( \theta = \sin^{-1} \left( \frac{x - 2}{2} \right) \), yielding:
\[
\sin^{-1} \left( \frac{x - 2}{2} \right) + C.
\]